HEREDITARIEDADE E REPETIÇÃO NO ATO SUICIDA: UMA ABORDAGEM PSICANALÍTICA - Nunes Lima, Felipe; Saleme Maciel Gondim, Denise (LINKSCIENCEPLACE, 2026)
The suicide is a complex phenomenon that has not an universal explanation. It is an exclusively human manifestation that occurs in every culture. In the search for understanding this phenomenon heredity has been pointed out as an important risc fator to suicidal acts. This paper discuss the problem of repetition of the suicidal acts throghout generations from a psychoanalitical perspective. Based on Freud‟s and Lacan‟s studies on the concept of identification, we concieve the suicidal act and the inclination for self-agression as a trait that can be used as a support for identification. Thus, it is possible to speak of a process of psychic transmission through which the suicidal act can repeat itself for generations. Due to the fact that the experience of satisfaction is always incomplete, the subject will aim repeating it seacrhing for the traits of the object which marked him, identifying himself to them, perpetuating the movement of compulsion to repetition. We also saw the importance of identification as determinant to the formation of the supergo, an instance that plays a fundamental role on the suicidal act, since it is it that allows the Ego to be treated like an object.